Refugee Resettlement in Australia: What we know and need to know - Fozdar, F.; Hartley, Lisa (Oxford University press, 2013)
The year 2011 marked the 60th anniversary of the United Nations Refugee Convention. It is thus an appropriate time to review the situation of refugees in one of the few signatory countries that accepts United Nations High Commissioner for Refugees-approved refugees, Australia. Australia takes around 14,000 refugees annually, from countries in the African, Middle Eastern, and Asian regions. The Australian Government funds a range of services to assist the settlement process, and these are recognized as among the best in the world. While these services provide assistance in the areas of employment, education and training, housing, language, health, social support, and cultural orientation, there is room for improvement to ensure social inclusion. This article provides an overview of research undertaken with this population over the last 15 years investigating some of the key barriers to social inclusion. It outlines a number of matters in need of policy improvement, and areas for further research.